Empirical analysis of the global supply and demand of entrepreneurial finance: A random utility theory perspective - Ibrahim Niankara (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Considering the globalized nature of international financial markets and the important role of innovative entrepreneurial endeavors for employment and economic development, this paper analyzes the global supply and demand of entrepreneurial finance, in the form of individuals' savings and borrowings for entrepreneurial ventures in the global economy. To this end, a theoretical treatment of the potential global entrepreneurial finance market (GEFM) dynamics, in response to governments and private sector financial transfers, is first provided. This is followed by the econometric modeling of such dynamics based on intertemporal random utility maximization, using pooled data from the 2014 and 2017 global financial inclusion surveys. The findings reveal, contrary to theoretical predictions, that private sector financial injections (i.e., electronic wage payments), exert an adverse effect on the GEFM; meanwhile, in accordance with theoretical predictions, public sector financial injections (i.e., electronic welfare payments), do positively influence the growth of the GEFM. In addition, compared to their male counterparts, females are found to be 7% more likely to own a formal account, and are 23.4% more likely to save for farming or business entrepreneurship, while also being 18.8% more likely to borrow for entrepreneurial ventures, therefore suggesting a relatively greater growth potential from female entrepreneurship in the global economy.
Keywords: 650; entrepreneurship; behavioral economics; discrete choice model; entrepreneurial finance; financial inclusion; small business finance